Hubungan Pengetahuan dengan Sikap Ibu dalam Pemberian MP-ASI pada Bayi Usia 7-12 Bulan dI Desa Togide’u Kecamatan Sirombu Kabupaten Nias Barat - Elvi Era Liesmayani; Mayang Citra Lestrari; Ade Sudiar (Jurnal Bidan Mandiri, 2024)
Background. The provision of complementary foods for breast milk (MP-ASI) is a reliable means to build quality human resources, because complementary foods for breastfeeding are one of the foods that guarantee the growth and development of babies. Research purposes. The purpose of this study was to determine the relationship between mother's knowledge and attitudes in providing complementary feeding for infants aged 7-12 months. Research design. Using descriptive method of cross sectional correlation design. Sample. A total of 31 respondents with the total population technique. Instruments. The mother's knowledge questionnaire and checklist sheet were used. Data analysis. Performed by means of univariate and bivariate analysis. Results. Knowledge of mothers in Togide'u Village, Sirombu District, West Nias Regency, shows that the majority have good knowledge of complementary foods, namely 16 (51.6%) people. The attitude of mothers in providing complementary feeding in Togide'u Village, Sirombu District, West Nias Regency, shows that the majority of mothers have a positive attitude, namely as many as 24 (77.4%) people. Conclusion. There is a relationship between mother's knowledge on attitudes in providing complementary feeding to infants aged 7-12 months in Sirombu Village, Sirombu District, West Nias Regency with p value = 0.001 <0.05. Suggestion. It is expected for mothers to provide complementary foods for breast milk to their babies appropriately because the baby's health is influenced by the nutrients absorbed in the body and is closely related to the food consumed.